Understanding Impulsive Buying Behavior in Marketplace - Didit Darmawan; John Gatheru (Journal of Social Science Studies (JOS3), 2021)
In the world, especially in Indonesia, e-commerce as a trading system using internet media has developed rapidly. Marketplaces such as Shopee, Blibli, Lazada, Tokopedia, Bukalapak, and others have contributed to improving online shopping behavior in Indonesia. Online trading transactions are also increasing and becoming a trend in society. Impulsive buying behavior arises as a result of the existence of an easy and practical online shopping system. This study aims to determine the effect of security, ease of use and trust on impulsive buying behavior. The population in this study were consumers who had made online purchases at Shopee and the sample was taken by purposive sampling of 100 people. The analysis tool uses multiple linear analysis. The results showed that the security variable had a significant and dominant positive effect on impulsive buying behavior; (2) ease of use has a significant effect on impulsive buying behavior; (3) trust has a significant effect on impulsive buying behavior. In addition, simultaneously, the three independent variables also have a significant influence on impulsive buying behavior at shopees.